Quantum simulation of a heterojunction vertical tunnel FET based on 2D transition metal dichalcogenides. (February 2016) - Cao, Jiang; Cresti, Alessandro; Esseni, David; Pala, Marco
Highlights: We simulate tunnel FET based on two-dimensional transition metal dichalcogenides. Our self-consistent simulations are based on the NEGF approach in the presence of phonon scattering. We clarify the role of some design parameters and indicate how to optimize them. We analyze the scalability of the device and evaluate some simple metrics. We show that TMD-TFETs are extremely promising for low-power applications. Abstract: We simulate a band-to-band tunneling field-effect transistor based on a vertical heterojunction of single-layer MoS2 and WTe2, by exploiting the non-equilibrium Green's function method and including electron–phonon scattering. For both in-plane and out-of-plane transport, we attempt to calibrate out models to the few available experimental results. We focus on the role of chemical doping and back-gate biasing, and investigate the off-state physics of this device by analyzing the influence of the top-gate geometrical alignment on the device performance. The device scalability as a function of gate length is also studied. Finally, we present two metrics for the switching delay and energy of the device. Our simulations indicate that vertical field-effect transistors based on transition metal dichalcogenides can provide very small values of sub-threshold swing when properly designed in terms of doping concentration and top-gate extension length.